Assessing the Impact of Sustainable Construction Practices on Project Performance. - Niwahereza, Blair (Kabale University, 2024)
The purpose of this research was to assess the impact of sustainable construction practices on project performance. Questionnaire surveys were conducted across stakeholders that included site engineers, consultants and contractors. The research categorized the proposed strategies to the implementation of sustainable construction practices using relative importance index (RII) as a basis of analysis. The most commonly used sustainable construction practices were identified as; use of local materials, use of bio-degradable materials, use of recycled materials, prefabrication and water conservation measures. Out of the 56 respondents, 16.1% were familiar with prefabrication, 14.3% were familiar with the use of bio-degradable materials, 28.6% were familiar with the use of water conservation measures, and 8.9% were familiar with the use of recycled materials and 32.1% constituted to those who were familiar with the use of local materials. The relationship between sustainable construction practices and project performance was critically determined using regression analysis and project performance was basically based on time, cost and quality. The general response from both parties were analyzed, high scored mitigation measures were discussed; awareness and education should be implemented, innovation and technology adoption; industry collaboration and partnerships, certification and standards, performance monitoring and reporting, and providing incentives were identified as the most effective strategies in implementing sustainable construction practices on construction projects. Awareness and education was ranked first with RII of 0.875, innovation and technology adoption was ranked second with RII of 0.857, industry collaboration and partnerships was ranked third with RII of 0.811, certification and standards was ranked fourth with RII of 0.807, performance monitoring and reporting was then ranked last with RII of 0.725.